Development of a new SETARA rating model: an application of the analytic hierarchy process - Islam, Rafikul; Anis, Azilah (IIUM, 2019)
SETARA, a rating tool was developed by the Malaysian Ministry of Higher Education in 2005 to rate the Malaysian universities - public as well as private. Over the years, the tool has been applied with considerable success. The tool comprises a comprehensive, all-encompassing criteria set along with their corresponding weights. However, how the weights have been determined and assigned to the criteria is not clear. It is well known that the set of weights affects the rating of a university significantly; so, it must be determined objectively. This research works has applied Analytic Hierarchy Process, a scientific prioritisation method, to compute the weights of various criteria and sub-criteria of SETARA assessment instrument. The new set of weights are computed using judgements taken from people involved in higher education administration and a scientific prioritisation method, therefore, it is claimed that the new set of weights is valid and acceptable. Upon comparison of the newly determined weights with the existing ones, significant differences are observed for certain criteria. This comparative analysis makes the main theme of this article.